Long-Term Outcomes of Excimer Laser-Assisted Penetrating Keratoplasty Using a Commercially Available Laser System – A Retrospective Case Series - Daniel, Moritz Claudius; Jiang, Jana; Lang, Stefan J.; Lapp, Thabo; Gross, Nikolai; Wacker, Katrin; Böhringer, Daniel; Maier, Philip; Reinhard, Thomas (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Favorable functional outcomes have been reported after excimer laser-assisted penetrating keratoplasty (EXL PKP). But this technique has not been widely adopted, and there are reports on EXL PKP from only a very limited number of institutions. Some of these results refer to operations carried out with laser systems that are not commercially available. In this retrospective case series, we report the long-term outcome of EXL PKP using the Schwind Amaris 500E laser system.Material and Methods This retrospective consecutive case series included 30 eyes of 29 patients who had undergone EXL PKP between 2010 and 2013. Primary outcome measures were topographic astigmatism and visual acuity. Secondary outcome measures were the rates of graft rejection and graft failure, and the rate of grafts with an endothelial cell density below 500 cells/mm2. Survival analyses were carried out for the following endpoints: visual acuity, rate of graft rejection, and rate of grafts with endothelial cell densities higher than 500 cells/mm2.Results The median interquartile range (IQR) duration of follow-up was 45 (36) months. The indications for PKP were keratoconus (n = 21), corneal scarring (n = 6), Fuchs endothelial dystrophy (n = 1), and corneal dystrophy other than Fuchs endothelial dystrophy (n = 2). The median (IQR) topographic astigmatism at the end of the follow-up period was 5.3 (2.9) D. Forty-five months after surgery, 73% of all eyes had a visual acuity better than 0.3 LogMAR. The rate of graft rejection after 45 months of follow-up was 32%. All eyes maintained endothelial cell densities higher than 500 cells/mm2. There was no graft failure.Conclusions EXL PKP is a safe and effective surgical procedure. No general conclusions can be drawn on the refractive outcome of EXL PKP. Potential advantages, such as a higher degree of graft-host congruity, that could possibly improve the refractive outcome should be weighed against the higher costs of EXL PKP.
Keywords: femtosecond laser; laser-assisted penetrating keratoplasty; penetrating keratoplasty; corneal transplantation; keratoconus; excimer laser